2003
DOI: 10.1007/s00467-002-0862-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal urinoma as a sign of a dysplastic kidney

Abstract: We describe a female neonate in whom a urinoma was first diagnosed at 20 weeks of gestation without any evidence of underlying urinary tract obstruction. The urinoma became apparent following the performance of a "bloody tap" amniocentesis. Sequential ultrasonography, both fetal and up to 3 months after birth, showed eventual resorption of the urinoma in parallel with the development of a shrunken, non-functioning kidney. Except for the onset of high-renin hypertension, which spontaneously remitted at 1 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…A fetal urinoma is a rare but important finding 3 . Diagnosis is primarily by prenatal ultrasound but further information can sometimes be elicited by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A fetal urinoma is a rare but important finding 3 . Diagnosis is primarily by prenatal ultrasound but further information can sometimes be elicited by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The occurrence of fetal urinomas has also been reported following a traumatic amniocentesis. [4] Additionally, Zaccara et al [11] reported three cases of fetal urinomas in female fetuses without an identifiable obstructive uropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] According to the current literature, it is more difficult to preserve renal function in cases of fetal urinomas than in their adult counterparts. [3][4][5][6][7][8] In our study, we reviewed the functional prognosis of kidneys with prenatally diagnosed urinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Since prenatal diagnosis was negative, the etiology was deemed to be secondary to trauma during delivery [7] . In the second case, reported by Miller et al in 2001, a perirenal fluid collection was due to traumatic amniocentesis [4] . In the third case, only gross vesico-ureteral reflux was documented [8] .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, urinoma without underlying obstruction in a low-pressure system, as in the female, has been reported only as a complication of amniocentesis [4] . Three cases without any apparent mechanism of formation are described herein.…”
Section: Introductionmentioning
confidence: 99%